Pengaruh Penerapan Strategi Pembelajaran Inkuiri Terhadap Kekurangan Sikap Berpikir Kritis dan Kreativitas Siswa SD - Indah Cahaya Putri; Shela Andri Mauliddina; Syifaun Nafisah; Prihantini Prihantini (Jurnal ini diterbitkan oleh: PGSD FKIP Universitas Muhammadiyah Tasikmalaya, 2023)
This study aims to analyze the effect of applying inquiry learning strategies to the lack of critical thinking andcreativity in elementary school students. The method used is a qualitative method based on the results ofliteratureresearch, namely collecting data from books, journals, theses, and others related to the relationship in the discussion. Elementary Student Creativity. In its implementation, this inquiry approach trains students on problems that have intellectual challenges and is planned in activities whose purpose is to guide children to be able to find something for themselves.